STUDY OF THE CONCEPT IN HISTORICAL, CULTURAL,ETHNOGRAPHIC AND LINGUISTIC ASPECTS - Khudoyarova Mukhayyo Rustamjon kizi (Western European Studies, 2025)
This article provides a brief overview of the history of the study and consideration of such a complex and multi-layered concept as "concept"in philological sciences and beyond: it is proposed to look at this term from the point of view of history, culture and ethnography.
Keywords: Concept; Conceptology; Concept In Ethnography; Concept In History